1996
DOI: 10.1093/infdis/174.4.812
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Subtypes and Antifungal Susceptibilities of Serial Cryptococcus neoformans Isolates in Human Immunodeficiency Virus-Associated Cryptococcosis

Abstract: Serial isolates of Cryptococcus neoformans from 33 human immunodeficiency virus-infected patients with cryptococcosis were analyzed to determine whether persistence might result from reinfection with a new cryptococcal strain or acquisition of antifungal resistance. Isolates were subtyped by multilocus enzyme electrophoresis (MEE), electrophoretic karyotyping (EK), random-amplified polymorphic DNA (RAPD), and the CNRE-1 DNA probe, MICs of amphotericin B, fluconazole, and 5-fluorocytosine were determined. No ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
65
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 22 publications
7
65
0
Order By: Relevance
“…In 1995, Haynes et al reported that paired isolates were genetically distinct in three of five individuals with HIV and cryptococcosis and suggested that this represented dual infection (14). Subsequently, a larger study of serial isolates from 33 individuals with HIV documented the persistence of a single C. neoformans isolate and failed to find evidence for dual infection or reinfection with a second strain (2). Nevertheless, additional instances of dual infections and acquisition of a second strain of C. neoformans have been described (16,21,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…In 1995, Haynes et al reported that paired isolates were genetically distinct in three of five individuals with HIV and cryptococcosis and suggested that this represented dual infection (14). Subsequently, a larger study of serial isolates from 33 individuals with HIV documented the persistence of a single C. neoformans isolate and failed to find evidence for dual infection or reinfection with a second strain (2). Nevertheless, additional instances of dual infections and acquisition of a second strain of C. neoformans have been described (16,21,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…neoformans, where mixed results have been seen. Multilocus enzyme electrophoresis (MLEE), electrophoretic karyotyping, and DNA sequence analysis all demonstrated few genotypes over a wide geographic region (3,15,42); the explanation for this was extensive clonal propagation of C. neoformans var. neoformans on pigeon guano and the worldwide expansion of the pigeon population.…”
Section: Discussionmentioning
confidence: 99%
“…Current regimens for treatment of the disease remain focused on amphotericin B, with or without flucytosine, for induction treatment, while fluconazole remains the agent of choice for long-term maintenance treatment (6,17,23). Previous studies have demonstrated that most recurrences of cryptococcal meningitis during maintenance therapy were due to the persistence of the original infecting strains rather than reinfection with a new cryptococcal strain (5,8,21). The MICs for serial isolates from patients with persistent cryptococcosis generally did not change significantly, and strains resistant to fluconazole were infrequently isolated from these patients during episodes of recurrent cryptococcal meningitis (5,6,8).…”
mentioning
confidence: 94%
“…Previous studies have demonstrated that most recurrences of cryptococcal meningitis during maintenance therapy were due to the persistence of the original infecting strains rather than reinfection with a new cryptococcal strain (5,8,21). The MICs for serial isolates from patients with persistent cryptococcosis generally did not change significantly, and strains resistant to fluconazole were infrequently isolated from these patients during episodes of recurrent cryptococcal meningitis (5,6,8). However, concerns regarding fluconazole-resistant strains of C. neoformans have been expressed by several investigators (1, 4, 5, 6, 24; J. P. Viard, C. Hennequin, N. Fortineau, N. Pertuiset, C. Rothschild, and H. Zylberberg, Letter, Lancet 346:118, 1995).…”
mentioning
confidence: 99%